Modelling of European hake nurseries in the Mediterranean Sea: An ecological niche approach. (January 2015) - Druon, Jean-Noël; Fiorentino, Fabio; Murenu, Matteo; Knittweis, Leyla; Colloca, Francesco; Osio, Chato; Mérigot, Bastien; Garofalo, Germana; Mannini, Alessandro; Jadaud, Angélique; Sbrana, Mario; Scarcella, Giuseppe; et al.
Highlights: A potential habitat of 0-group hake at the scale of the Mediterranean Sea is proposed. The model links ecological traits of 0-group hake and environmental variables. Chlorophyll-a fronts are used as a proxy for food availability for hake nurseries. Temperature and currents at seabed define the environmental tolerance of hake nurseries. The ENM model describes potential nurseries in areas where no studies are available. Abstract: An ecological niche modelling (ENM) approach was developed to model the suitable habitat for the 0-group European hake, Merluccius merluccius L., 1758, in the Mediterranean Sea. The ENM was built combining knowledge on biological traits of hake recruits (e.g. growth, settlement, mobility and feeding strategy) with patterns of selected ecological variables (chlorophyll-a fronts and concentration, bottom depth, sea bottom current and temperature) to highlight favourable nursery habitats. The results show that hake nurseries require stable bottom temperature (11.8–15.0 °C), low bottom currents (<0.034 m s −1 ) and a frequent occurrence of productive fronts in low chlorophyll-a areas (0.1–0.9 mg m −3 ) to support a successful recruitment. These conditions mostly occur recurrently in outer shelf and shelf break areas. The prediction explains the relative balance between biotic and abiotic drivers of hake recruitment in the Mediterranean Sea and the primary role of unfavourable environmental conditions on low recruitment in specific years (i.e. 2011). The ENM outputs particularly agree spatially with biomass data of recruits, although processes such as fishing and natural mortality are not accounted for. The seasonal mapping of suitable habitats provides information on potential nurseries and recruitment carrying capacity which are relevant for spatial fisheries management of hake in the Mediterranean Sea.